Minangkabau Women in the Novel Mengurai Rindu by Nang Syamsuddin - Aimifrina, Aimifrina (KnE Social Sciences, 2022)
This study aimed to examine the Minangkabau women in the novel Mengurai Rindu by Nang Syamsuddin. Minangkabau women are seen from the view of people in the Minangkabau culture. The results of the study suggested that Minangkabau women include parents. Minangkabau women are prominent in society, becoming leaders or elders in their environment, with professional and functional duties. The results of this study are in accordance with the matrilineal cultural system adopted by the Minangkabau community. Keywords: women, real person, novel